The fibrinogen levels on admission is a predictive marker of the contrast extravasation on enhanced computed tomography in sacral fracture. Issue 10 (12th March 2021) - Notani, Naoki; Miyazaki, Masashi; Kanezaki, Shozo; Ishihara, Toshibobu; Sakamoto, Tomonori; Abe, Tetsutaro; Kataoka, Masashi; Tsumura, Hiroshi
Abstract : Abstract: Sacral fracture is the most frequent posterior injury among unstable pelvic ring fractures and is prone to massive hemorrhage and hemodynamic instability. Contrast extravasation (CE) on computed tomography (CT) is widely used as an indicator of significant arterial bleeding. However, while CE is effective to detect significant arterial bleeding but negative result cannot completely rule out massive bleeding. Therefore, additional factors help to compensate CE for the prediction of early hemodynamically unstable condition. We evaluated the risk factors that predict CE on enhanced computed CT in patients with sacral fractures. Patients were classified into 2 groups: CE positive on enhanced CT of the pelvis [CE(+)] and CE negative [CE(−)]. We compared age, sex, injury severity score (ISS), systolic blood pressure (sBP), type of sacral fracture based on Denis classification, platelet (PLT), base excess, lactate, prothrombin time-international normalized ratio, hemoglobin (Hb), activated partial thromboplastin time, D-dimer, and fibrinogen between the 2 groups. A total of 82 patients were treated for sacral fracture, of whom 69 patients were enrolled. There were 17 patients (10 men and 7 women) in CE(+) and 52 patients (28 men and 24 women) in CE(−). Age, ISS, and blood transfusion within 24 hours were significantly higher in the CE(+) group than in the CE(−) group ( P  = .023, P  < .001, P  < .001). sBP, Hb, PLT, fibrinogen were significantly lower in the CE(+) group than in the CE(−) group ( P  < .001, P  < .001, P  < .001, P  < .001). D-dimer and lactate were higher in the CE(+) group than in the CE(−) group ( P  = .036, P  < .001) with significant differences. On multivariate analysis, the level of fibrinogen was an independent predictor of CE(+). The area under the curve value for fibrinogen was 0.88, and the optimal cut-off value for prediction was 199 mg/dL. The fibrinogen levels on admission can predict contrast extravasation on enhanced CT in patients with sacral fractures. The optimal cut-off value of fibrinogen for CE(+) prediction in sacral fracture was 199 mg/dL. The use of fibrinogen to predict CE(+) could lead to prompt and effective treatment of active arterial hemorrhage in sacral fracture.